Service Quality for Facilities Management in Hospitals - Sui Pheng, Low.; Rui, Zhu.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book examines the Facilities Management (FM) of hospitals and healthcare facilities, which are among the most complex, costly and challenging kind of buildings to manage. It presents and evaluates the FM service quality standards in Singapore's hospitals from the patient's perspective, and provides recommendations on how to successfully improve FM service quality and achieve higher patient satisfaction. The book also features valuable supplementary materials, including a checklist of 32 key factors for successful facilities management and another checklist of 24 service attributes for hospitals to achieve desirable service quality in connection with facilities management. The book adopts a unique approach of combining service quality and quality theory to provide a more holistic view of how FM service quality can be achieved in hospitals. It also integrates three instruments, namely the SERVQUAL model, the Kano model and the QFD model to yield empirical results from surveys for implementation in hospitals. Although the book was written from the perspective of FM service quality for hospitals, the findings and recommendations are also relevant for other non-healthcare sectors where appropriate lessons may also be drawn for FM and service quality in general. It will particularly benefit Quality Managers, Facilities Managers and Hospital Administrators.
Introduction -- Facilities Management and Singapore's Healthcare System -- SERVQUAL, the Kano model and QFD -- Conceptual Framework -- Research Methodology -- Data Analysis -- Discussions -- Conclusions.
Keywords: Facility management; Practice of medicine; Hospitals -- Administration; Health services administration; Facility Management; Practice and Hospital Management; Health Care Management